Frequency-Dependent Reaction of the Triceps Surae Muscle of the Mouse During Electromyostimulation - Zart, Sebastian; Berger, Joshua; Ludwig, Oliver; Knauth, Janosch; Fröhlich, Michael (Frontiers in Physiology, 2020)
The difference in the efficacy of altered stimulation parameters in whole-body-electromyostimulation training (WB-EMS) has hardly been examined. Higher impulse frequencies (>50 Hz) might be most adequate for strength gains because of the force frequency relationship (FFR), which describes a greater force production by increasing the applied frequency. Frequencies below this value, however, also seem to have positive influences on muscle strength increases. Therefore, the aim of this study was to analyze possible muscle length changes to different stimulation frequencies of the dissected mouse triceps surae muscle. A bending rod transducer was used to measure and compare changes in muscle lengths at different frequencies in relation to the initial length in the prepared muscle. We found significant differences between the muscle shortening at different frequencies (p<0.001). At 20 Hz the largest muscle shortening was observed (20 Hz = 3.32 ± 2.06, 60 Hz =0.77 ± 0.58, 85 Hz = 0.32 ± 0.29, 100 Hz = 0.31 ± 0.29). From a frequency of 60 Hz, the muscle shortening decreased progressively, at stimulation frequencies above 60 Hz the lowest shortenings were recorded. The results demonstrate a different behavior of the isolated triceps surae muscle of the mouse in an ex vivo environment. Even if there is no FFR in this investigation, the results indicate a higher metabolic demand using higher frequencies in electromyostimulation, despite the experimental execution in ex vivo design. Therefore, future studies should take this faster fatigue into account when drawing up training protocols in order to counteract possible frequency modulations.